The Use of Learning Model Picture and Picture to Improve Understading Concept of Science - Muarofah, Lili Maryatul (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
Purpose of the research is to improve understanding concept of science of 5th grade students of SD Negeri Mintaragen 3 of Kecamatan Tegal Timur,Tegal of 2020/2021 academic year by using picture and picture. This research is classroom action research. The research uses collaboration between author and teacher of class V. Data is collected by using documentation, observation and test techniques. The research consists of 2 cycles and every cycle comprises four stages, namely: (1) action planning, (2) action implementation, (3) observation and (4) reflection. The research found that average grade before action (precycle) was 62.08 with classical completeness was 12.5%. At cycle I, classroom average grade achieved 70.41 and classical completeness was 50%. At cycle II, the average grade increased to 80.41 with classical completeness was 87.5%, it can be concluded that the use of Picture and Picture can improve understanding concept of science.